Reflections on environmental education, from the perspective of human rights education, and its influence on the culture of captivity of wildlife - Santiago , Adelquis Stanley Monteiro; Monteiro , Adriana Kirley Santiago; Santiago , Andrea Karine de Araújo (Seven Editora, 2023)
This theoretical essay explores the relationship between Human Rights Education (HRE) and Environmental Education (EA) in the context of wildlife protection and human health. Through the analysis of scientific publications on the interaction between HRE and EA, along with reflections based on the experiences of one of the authors as a Federal Environmental Agent, the need for a cultural change in relation to captivity and wildlife trafficking is examined. In Brazil, wildlife trafficking has historical roots and is associated with cultural, social and economic problems. The persistent belief that keeping wild animals as pets is an act of love perpetuates a culture of captivity. However, raising awareness of society through HRE and EA is key to addressing this issue. The study reports positive experiences of raising awareness of the population through educational actions, including lectures in schools and the promotion of the voluntary delivery of animals to the Brazilian Institute of the Environment and Renewable Natural Resources (IBAMA). These initiatives demonstrate the transformative potential of education in cultural change regarding the maintenance of wildlife in captivity. Still, there are challenges to be overcome, such as the lack of investment and appreciation of EA in public policies. For HRE and EE to be effective, greater investment in the training of educators in these areas is essential. In conclusion, the importance of EE based on HRE for sustainable development and the need for comprehensive public policies in this direction are highlighted. DOI:https://doi.org/10.56238/Connexpemultidisdevolpfut-109